(untitled) (Revista Iberoamericana de Bioética, 2020)
The paper argues that, for the most part, disasters are not natural. Although natural hazards normally affect all residents of a geographical area, they are rarely affected to the same degree, given that social vulnerability is unequally distributed in most societies. Social vulnerability is causally related to the distribution of wealth, power, and social status in society, therefore, its distribution is a social justice issue. This paper also analyses the connections between climate change and the increased risk of climate disasters. Pope Francis’ “integral ecology” is proposed as a path to the future.